Pengaruh Nilai Tukar dan Harga Teh Internasional terhadap Nilai Ekspor Teh Indonesia - Raden Vannessa Hind Ganeswara (Jurusan Ilmu Ekonomi Universitas Katolik Parahyangan, 2025)
Indonesia is one of the world's top producers and exporters of tea, making it a vital commodity for the country's economy. But over the previous 18 years, the value of Indonesia's tea exports has decreased. This study uses the Ordinary Least Squares (OLS) method to determine the factors influencing the value of tea exports between 1980 and 2020. The findings show that the value of tea exports is significantly impacted negatively by land area, exchange rates, and the GPATN policy. On the other hand, international tea prices and production have a major positive impact.